Individual Differences in Political Ideology and Disgust Sensitivity Affect Real-Time Spoken Language Comprehension - Hubert Lyall, Isabell; Järvikivi, Juhani (Frontiers in Psychology, 2021)
Individuals’ moral views have been shown to affect their event-related potentials (ERP) response to spoken statements, and people’s political ideology has been shown to guide their sentence completion behavior. Using pupillometry, we asked whether political ideology and disgust sensitivity affect online spoken language comprehension. 60 native speakers of English listened to spoken utterances while their pupil size was tracked. Some of those utterances contained grammatical errors, semantic anomalies, or socio-cultural violations, statements incongruent with existing gender stereotypes and perceived speaker identity, such as ``I sometimes buy my bras at Hudson's Bay'', spoken by a male speaker. An individual's disgust sensitivity is associated with the Behavioral Immune System, and may be correlated with socio-political attitudes, for example regarding out-group stigmatization. We found that more disgust-sensitive individuals showed greater pupil dilation with semantic anomalies and socio-cultural violations. However, political views differently affected the processing of the two types of violations: whereas more conservative listeners showed a greater pupil response to socio-cultural violations, more progressive listeners engaged more with semantic anomalies, but this effect appeared much later in the pupil record.